Rhetoric and speculative grammar: school method and grammatical discourse - Beccari, Alessandro Jocelito [UNESP] (Univ Estadual Oeste Parana-unioeste, 2018)
Quintilian (ca. 35-96 CE) in his book Institutio Oratoria consolidated the Greco-Roman rhetorical doctrine in a systematic way and determined the outline of a teaching system that had the dexterity in the art of persuasion as its goal and crowning. Roman Rhetoric was adapted by the Church Fathers (2nd-8th century AD) to fit the needs of Christian preaching and apologetics, and its teaching and learning led to the emergence of the Scholastic Method. Thus, it is from Roman Rhetoric that the guidelines for the medieval scientific discourse originated, of which speculative grammar, as scientia sermonicalis (theoretical knowledge about discourse) makes privileged use. The genre of the summae, such as the Summa theologicae of Thomas Aquinas (1224-1275) and the summae of grammar such as Thomas of Erfurt's Speculative grammar (ca. 1310), have a structure that reveals the genre of the spoken debate known as the disputed question, a true tournament of rhetorical argumentation based on Aristotelian Syllogistics. This article aims to demonstrate how the grammatical works of the modistae belonged to a common rhetorical tradition of disputes and commentaries that was at the basis of the universe of teaching and learning of the universities of Medieval Europe. For a contextualization of Rhetoric and Medieval Philosophy, we will use Ullmann (2000), Gilson (1996), De Libera (1990), Tringali (1988), Aristotle's Rhetoric and Thomas Aquinas' Summa theologiae. Our historiographical discussions are guided by the ideas and models of Covington (1984) and Koerner (1989).
Keywords: Rhetoric; Middle Ages; Speculative Grammar